Uptake rates of novel therapies and survival among privately insured versus publicly insured patients with colorectal cancer in Germany - Jansen, Lina; Boakye, Daniel; Alwers, Elizabeth; Carr, Prudence R.; Reißfelder, Christoph; Schneider, Martin; Martens, Uwe Marc; Chang-Claude, Jenny; Hoffmeister, Michael; Brenner, Hermann (Journal of the National Comprehensive Cancer Network, 2021)
Background: In the era of personalized medicine, cancer care is subject to major changes and innovations. It is unclear, however, to what extent implementation of such innovations and their impact on patient outcomes differ by health insurance type. This study compared provision of treatment and survival outcomes among patients with colorectal cancer (CRC) who had statutory health insurance (SHI) versus private health insurance (PHI) in Germany. Methods: We analyzed patterns of CRC treatment (surgery, chemotherapy/radiotherapy, and targeted therapy) and survival in a large cohort of patients who were diagnosed with CRC in 2003 through 2014 and were observed for an average of 6 years. Associations of type of health insurance with treatment administration and with overall, CRC-specific, and recurrence-free survival were investigated using multivariable logistic and Cox proportional hazards models, respectively. Results: Of 3,977 patients with CRC, 427 (11%) had PHI. Although type of health insurance was not associated with treatment administration in patients with stage I-III disease, those with stage IV disease with PHI more often received targeted therapy (65% vs 40%; odds ratio, 2.43; 95% CI, 1.20-4.91), with differences decreasing over time because of catch-up of uptake rates in patients with SHI. Median overall survival was longer in patients with PHI than in those with SHI (137.0 vs 114.9 months; P=.010), but survival advantages were explained to a large extent by differences in sociodemographic factors. In patients with stage IV disease, survival advantages of PHI were nonsignificant and were restricted to the early years after diagnosis. Conclusions: We observed major differences in uptake of targeted therapy between patients with PHI and those with SHI but no differences in patient survival after adjusting for relevant sociodemographic, clinical, and tumor characteristics. Further studies are needed on factors associated with the uptake of therapeutic innovations and their impact on patient survival by health insurance type.
Gesehen am 26.07.2021